The Thuli and Cele paramountcies in the coastlands of Natal, c. 1770 - c. 1820 - Wright, J. (Southern African Humanities, 2021)
The literature on the history of what is now the KwaZulu-Natal region in the seventy years or so before the rise of the Zulu Kingdom under Shaka in the 1810s and 1820s has generally focussed on the rivalries between the Ndwandwe, Mthethwa, Swazi and - to a lesser extent - Mabhudu chiefdoms. In geographical terms, the focus has been on the region between the middle Nkomati river in the north and the Thukela river in the south. Historians have paid comparatively little attention to events in the peripheries of this 'core' region. The present article describes political developments in the coastlands of its southern periphery in the late eighteenth and early nineteenth centuries, developments which saw the establishment of two expanded chiefdoms under the domination respectively of the Thuli and, a little later, of the Cele. The longer-term significance of these events is that they were instrumental in shaping Shaka's policies of expansion south of the Thukela after 1820. To cite this article: Wright, J. 2009. The Thuli and Cele paramountcies in the coastlands of Natal, c. 1770 - c. 1820. Southern African Humanities 21: 177-194.